Pengaruh Tatakelola terhadap Pengungkapan Lingkungan - Ade Samsul Saripudin; Neneng Lasmita Susanti (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
This study aims to examine the impact of corporate governance on environmental disclosure, with firm size and leverage as control variables. A quantitative research method is employed, utilizing secondary data in the form of annual financial reports from companies listed on the Indonesia Stock Exchange (IDX). The research focuses on energy sector companies listed on the IDX from 2020 to 2022. Data analysis is conducted using statistical techniques, specifically multiple linear regression. Logistic regression analysis is performed using SPSS V22 software. The sample is selected through purposive sampling, based on specific criteria. The study spans a four-year period from 2020 to 2022, involving 35 companies and a total of 105 observations. The results, obtained through multiple regression analysis, indicate the following: institutional ownership does not influence environmental disclosure, independent commissioners have no impact on environmental disclosure, the audit committee has a significant effect on environmental disclosure, firm size does not affect environmental disclosure, and leverage also has no impact on environmental disclosure.